Nurse telephone education for promoting a treat‐to‐target approach in recently diagnosed rheumatoid arthritis patients: A pilot project. (5th December 2018) - Farley, Siobhan; Libman, Bonita; Edwards, Melinda; Possidente, Carl J.; Kennedy, Amanda G.
Abstract: Objective: The aim of the present study was to implement a nurse telephone education programme for patients with recently diagnosed rheumatoid arthritis (RA) that promotes shared decision‐making and a treat‐to‐target approach. Methods: This was a pilot project of newly diagnosed adult RA patients conducted between November 2015 and December 2016. A rheumatology clinic nurse telephoned patients to offer disease education. A toolkit was mailed to patients. Measures included call attempts, call time, a qualitative description of free‐text notes and the proportion of patients who adhered to their next clinic visit. Data were analysed descriptively and qualitatively. Results: Twenty‐six patients participated in the nurse calls. Most patients were female (65%), with a median age of 54 years (range 22–78 years). Median call length was 14.5 min, with a range of 8–23 min. Qualitative notes indicated that patients overwhelmingly supported the nurse calls. Nineteen patients (73%) were adherent to their follow‐up visit. Conclusion: This preliminary project successfully implemented an educational programme that included a nurse‐facilitated, RA‐specific, telephone call and toolkit. This educational programme could be a model for similar educational efforts by other clinics.